Cassava Starch Nanoparticles . A â€œnanocarrierâ€ for Anthocyanin and Carotene Delivery - L.S., RAJESWARI (JOURNAL OF ROOT CROPS, 2016)
Cassava is a tropical tuber crop useful in the production of high quality of starch economically. One interesting application of starch is in the preparation of starch nanocrystals and nanoparticles by acid hydrolysis. These nanoparticles possess a reactive surface covered with hydroxyl groups, providing the possibility of extensive chemical modification. Biodegradable nanoparticles have been recently suggested as controlled release constructs to mitigate the side effects caused by nonspecific action of cytotoxic drugs commonly employed in chemotherapy. In this connection, starch nanoparticles currently receive much attention because of the abundance and easy availability of starch, its low cost, renewability, biocompatibility, biodegradability, and nontoxicity. There are several research reports supporting the capacity of these nanoparticles as excellent candidates for implant materials and drug carriers. Anthocyanin, a flavanoid extracted from the leaves of sweet potato, is a very good natural chemo preventive agent that allows suppression, retardation or inversion of carcinogenesis. The chemo preventive effect of carotene is also well established. In the present work, the preparation of starch nanoparticles from cassava starch, their characterization using Transmission electron microscopy (TEM) and Atomic Force Microscopy (AFM) and their interaction with anthocyanin and carotene are attempted. The evidence for loading was provided Attenuated Total Reflectance (ATR) spectroscopy. These plant pigments with proven chemo preventive properties after incorporation into starch nanoparticles could possibly be used in pharmaceutical applications since these nanoparticles possess excellent drug carrier properties.